2017
DOI: 10.3390/s17102408
|View full text |Cite
|
Sign up to set email alerts
|

Command Disaggregation Attack and Mitigation in Industrial Internet of Things

Abstract: A cyber-physical attack in the industrial Internet of Things can cause severe damage to physical system. In this paper, we focus on the command disaggregation attack, wherein attackers modify disaggregated commands by intruding command aggregators like programmable logic controllers, and then maliciously manipulate the physical process. It is necessary to investigate these attacks, analyze their impact on the physical process, and seek effective detection mechanisms. We depict two different types of command di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…MQTT may also employ TLS for encryption via port 8883. More information on the security of industrial IoT systems can be found in [53][54][55], on intrusion detection in [56][57][58], on encryption in [59], and on black-hole detection in [60].…”
Section: Discussionmentioning
confidence: 99%
“…MQTT may also employ TLS for encryption via port 8883. More information on the security of industrial IoT systems can be found in [53][54][55], on intrusion detection in [56][57][58], on encryption in [59], and on black-hole detection in [60].…”
Section: Discussionmentioning
confidence: 99%
“…The system data security is the guarantee of the safe and reliable operation of industrial manipulators [20]. During a system data transmission process, attackers modified the state of the exchange between the master and slave manipulators by introducing a static malicious content modification attack, which made the joint speed of the manipulator unstable and realized the content modification attack of the bilateral teleoperation system [21].…”
Section: B System Datamentioning
confidence: 99%
“…Then, we destroy the data logic of B s in red line, and the values in blue line are the attacked system data in Equation (20).…”
Section: B Cosimulation Model 1) the Data Logic Attack Simulationmentioning
confidence: 99%
“…A tank system [7,31] is simulated by using Matlab/Simulink, and its structure is shown in Figure 8. The controller of the tank system receives requests from users to produce liquid C, E, F, and G by the neutralization process of ingredient A, ingredient B, and ingredient D. Liquid C is produced when the ratio of ingredient A to ingredient B is 1.…”
Section: Scenariomentioning
confidence: 99%